Pembuatan Nata De Pina Dari Limbah Kulit Nanas Dengan Proses Fermentasi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2023)
Pineapple skin (Ananas Comusus L. Merr) honey and queen is a waste that has the potential to be used as nata de pina. In making nata de pina, it is done by adding peanut sprout extract as an alternative nitrogen source, because peanuts have high carbohydrate and protein content. This study aims to determine the effect of adding peanut sprout extract in the manufacture of nata de pina. resulting from. The method of making nata de pina in this study was carried out by the fermentation process of Acetobacter Xylinum bacteria for 14 days with variations in the addition of peanut sprout extract (100 grams/200 ml, 150 grams/200 ml). The results showed that the queen type pineapple skin with the addition of 150 gram/200 ml peanut sprout extract was the best with the resulting nata de pina thickness of 1.5 cm and with the results of sugar content and fiber content approaching SNI 01-4317-1996. Keywords : peanut sprouts, pineaple skin, nata de pina skin